1995
DOI: 10.1063/1.469298
|View full text |Cite
|
Sign up to set email alerts
|

Classical trajectory studies of the reaction CH4+H→CH3+H2

Abstract: Articles you may be interested inMode specific dynamics of the H2 + CH3 → H + CH4 reaction studied using quasi-classical trajectory and eightdimensional quantum dynamics methods J. Chem. Phys. 143, 154307 (2015) Trajectory data are reported for the reaction CH 4 ϩH→CH 3 ϩH 2 , designed to provide information that can be used to test approximate quantitative theories for the dynamics of abstraction reactions. A potential function was devised which properly reflects the nuclear permutation symmetry of the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(84 citation statements)
references
References 39 publications
4
79
0
1
Order By: Relevance
“…It is much harder to treat synchronous bond breaking and bond forming, but this was also accomplished in the early days of quantum mechanics, resulting in the London equation [186][187][188]. Raff [189] was apparently the first to combine the valence-bond-derived QM London equation with molecular mechanics terms to make a QM/MM reactive potential, and in recent years many other workers, [190,191] especially Espinosa-Garcia and coworkers [192][193][194][195][196][197], have made fruitful use of this technique. Various workers, of whom we single out Brenner [198][199][200] and Goddard and coworkers [201][202][203][204] for noteworthy systematic efforts, have made generalizations to more complex reactive systems.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…It is much harder to treat synchronous bond breaking and bond forming, but this was also accomplished in the early days of quantum mechanics, resulting in the London equation [186][187][188]. Raff [189] was apparently the first to combine the valence-bond-derived QM London equation with molecular mechanics terms to make a QM/MM reactive potential, and in recent years many other workers, [190,191] especially Espinosa-Garcia and coworkers [192][193][194][195][196][197], have made fruitful use of this technique. Various workers, of whom we single out Brenner [198][199][200] and Goddard and coworkers [201][202][203][204] for noteworthy systematic efforts, have made generalizations to more complex reactive systems.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Since reactive and vibrational motion in the barrier region are usually strongly coupled, descriptions beyond the most simple harmonic approximation require truly multi-dimensional quantum dynamics calculations. Here it was found that the anharmonicities in principle have a sizeable effect on the zero point energies (e.g., around 0.5 kcal/mol for CH 4 [69,99] and the H +CH 4 transition state [70] at the Jordan-Gilbert PES [72]), but these effects cancel out quite well when the differences between the transition state energies and the reactant energies are considered [69,70]. Thus, approximate calculations can typically disregard such anharmonic effects as long as it is consistently done in the reactant partition function and the N (E) computation.…”
Section: Quantum Effects In Reaction Rates: Conclusionmentioning
confidence: 99%
“…While the above calculations could treat the quantum dynamics of the reaction process rigorously, still the underlying PES used in these calculations [72,73] were not accurate and resulted in significant differences between experiment and theory. Therefore the further development considered the construction of accurate full-dimensional PES which will be discussed in some more detail in Sect.3.…”
Section: From Triatomics To Polyatomic Reactionsmentioning
confidence: 99%
“…In the test calculations reported below we used the BoothroydKeogh-Martin-Peterson (BKMP2) potential energy surface for H + H 2 [47], the modified and recalibrated versions of the JordanGilbert [48] potential energy surface developed by EspinosaGarcía et al for H + CH 4 [49] and OH + CH 4 [50], and the combined valence bond-molecular mechanics (CVBMM) potential energy surface for H + C 2 H 6 [51]. (The last three potential energy surfaces were taken from the online POTLIB library [52].)…”
Section: Example Calculationsmentioning
confidence: 99%